2013
DOI: 10.1093/infdis/jit085
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte and Myeloid Dendritic Cell Activation Occurs Throughout HIV Type 2 Infection, an Attenuated Form of HIV Disease

Abstract: Monocytes and myeloid dendritic cells (mDCs) are important orchestrators of innate and human immunodeficiency virus (HIV)-specific immune responses and of the generalized inflammation that characterizes AIDS progression. To our knowledge, we are the first to investigate monocyte and mDC imbalances in HIV type 2 (HIV-2)-positive patients, who typically feature reduced viremia and slow disease progression despite the recognized ability of HIV-2 to establish viral reservoirs and overcome host restriction factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 50 publications
1
27
2
Order By: Relevance
“…Our results showing ISG induction after infection of IDCs with HIV-1 plus Vpx or HIV-2, which degrade SAMHD1 and allow reverse transcription, support a role for cGAS sensing under these conditions. Taking into consideration the different virulence of HIV-1 and HIV-2, our data confirm previous observations (22,37,45,48) suggesting that through restriction of replication in DCs, lentiviruses avoid triggering class I IFN responses. As a consequence and paradoxically, low infection of DCs would result in higher virulence due to escape from early immune surveillance, thereby allowing broader dissemination of infected cells.…”
Section: Chemokine Expression During MDC Infectionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our results showing ISG induction after infection of IDCs with HIV-1 plus Vpx or HIV-2, which degrade SAMHD1 and allow reverse transcription, support a role for cGAS sensing under these conditions. Taking into consideration the different virulence of HIV-1 and HIV-2, our data confirm previous observations (22,37,45,48) suggesting that through restriction of replication in DCs, lentiviruses avoid triggering class I IFN responses. As a consequence and paradoxically, low infection of DCs would result in higher virulence due to escape from early immune surveillance, thereby allowing broader dissemination of infected cells.…”
Section: Chemokine Expression During MDC Infectionsupporting
confidence: 89%
“…To validate the results observed in our models of productive HIV-1 infection in which Vpx was artificially loaded in viral particles, human DCs were infected with HIV-2 carrying the vpx gene, which increases productive infection in cells of the myeloid lineage (45)(46)(47). DCs were generated as described in Materials and Methods and infected with the HIV-2 ROM10 strain.…”
Section: Regulation Of Gene Expression In Dcs By Other Lentivirus Infmentioning
confidence: 84%
“…This was accompanied by upregulation of the immunoinhibitory molecules PD-L1/PD-1, leading the authors to suggest that this may be an explanation for the more benign outcome in those with HIV-2 infection. 21 In this study, we found no differences in sCD163 levels between HIV types at baseline or at follow-up among patients without ART. However, for patients on ART, HIV-2-infected patients had a significantly lower decrease in sCD163 levels than HIV-1-infected patients.…”
Section: Relations To Other Studies and Potential Biological Mechanismscontrasting
confidence: 53%
“…21 An increased monocyte activation in HIV-2 infection has previously been described. This was accompanied by upregulation of the immunoinhibitory molecules PD-L1/PD-1, leading the authors to suggest that this may be an explanation for the more benign outcome in those with HIV-2 infection.…”
Section: Relations To Other Studies and Potential Biological Mechanismsmentioning
confidence: 87%
“…LPS levels were elevated in an African cohort with HIV-2 infection and correlated with disease progression [88]. However, this was not observed in a European cohort, even though there was evidence of significant T cell and monocyte activation [89]. In marked contrast to HIV-1 infection, mucosal integrity and gut-associated lymphocyte numbers are preserved in aviraemic HIV-2 infection (with or without ART), despite the presence of replicating virus in the gut mucosa [82].…”
Section: Immune Activationmentioning
confidence: 91%